Effect of different disinfectants on preventing asymptomatic bacteriuria and catheter-related urinary tract infection: a network meta-analysis - Sun, Zhi Hong; Ma, Xue Wei; Sun, Wei; Wei, Ying Ji; Li, Yi Zhen; Wang, Dan; Zhou, Chang Xi; Xu, Guo Gang; Zhang, Gui Zhi (Frontiers in Urology, 2023)
Objective: To analyze the effect of variant types of disinfectants for perineum and urethral meatus cleaning in preventing catheter-associated asymptomatic bacteriuria and UTI catheter-associated urinary tract infection (CAUTI). Methods: The Chinese and English databases were searched to collect randomized controlled trials (RCTs) of variant disinfectants for perineum and urethral meatus cleaning to prevent CAUTI, and the positive rates of urine culture with variant cleaning methods were contrasted by network meta-analysis. Results: A total of 18 RCTs were included in this study to analyze the effect of 10 disinfectants in preventing CAUTI, which were 0. 1% chlorhexidine (CHG), 0. 5% CHG, 2% CHG, 0. 1% benzalkonium bromide (DBDAB), 0. 05% iodophor, 0. 5% iodophor, acidic oxidizing potential water (EOW), normal saline (NS), shehuang lotion lotion, and sterile water. Meta-analysis showed that the positive rate of urine culture in 0. 5% CHG cluster, EOW cluster, 0. 5% iodophor cluster and Shehuang lotion cluster was remarkably lower than that in 0. 1% DBDAB cluster (P < 0. 05), 0. 5% CHG cluster was remarkably lower than that in 0. 05% iodophor cluster (P < 0. 05), 0. 5% CHG cluster, 0. 5% iodophor cluster, Shehuang lotion cluster and EOW were remarkably lower than those in normal saline cluster (P < 0. 05), and 0. 5% CHG cluster and EOW cluster were remarkably lower than those in sterile water cluster (P < 0. 05). The results of the area under the cumulative ranking probability plot (SUCRA) analysis showed that the probability ranking of the preventive effect of variant disinfectants was as follows: 0. 5% CHG > shehuang lotion Lotion > EOW > 0. 5% Iodophor > 2% CHG > 0. 1% CHG > 0. 05% Iodophor > Sterile Water > 0. 1% DBDAB > Saline. Conclusion: 0. 5% CHG, Shehuang lotion, EOW and 0. 5% iodophor can be used to clean perineum and urethral meatus in patients with indwelling catheter.